H.761 Support of a DOM Level 4 Core specification in NCLua scripts - Guedes, Alan L. V.; Colcher, Sergio (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2019)
Web developers commonly run HTML template engines at the client-side using JavaScript. One upper hand is to give more development flexibility comparing to the server-side. In this way, we may cite web frameworks webcomponents, ReactJS, Vue, and others. Those frameworks use the DOM API to access the template data inserted in the HTML document. Then the same DOM API is used to insert more HTML code. Currently, NCL not support access to the current document. But it can modify the document by NCL Editing commands in NCLua scripts. We propose NCLua scripts partially support the DOM Code API.